Study on mechanical properties of large deformation segmental cement-based honeycomb structure - Gang Song; Ao Wang; Chengjun Hu; Chengjun Hu; Baofu Zhao; Hongwen Jing; Bo Meng; Zixuan Yu (Frontiers in Materials)
Honeycomb structures provide a new means of controlling and supporting the tunnel envelope. However, traditional honeycomb structures have low strength and poor stability, and are prone to stress concentration and instability, further limiting their application in deep tunnel support projects. In this paper, a new type of segmental cementitious honeycomb structure is investigated, its performance under different loading rates is tested, and its application in deep large deformation tunnel support is discussed. Firstly, the honeycomb model was drawn and the honeycomb skeleton was prepared. Then, the cement suspension technique was optimised. Secondly, the effects of different loading rates on the performance of segmented cement-bonded honeycomb structures were investigated by laboratory experiments. The results show that when the loading rate is 3 mm/min, the structure has the maximum load capacity and the best energy absorption performance. It is worth noting that too fast or too slow loading rate will affect the performance of the structure. Finally, the damage mechanism of the segmented honeycomb structure was further investigated by using an acoustic emission system, and the acoustic emission characteristics showed that the segmented cementitious honeycomb structure firstly went through a relatively stable stage of microcrack development under the action of the loads in all bands, and then a large area of damage was observed in the top layer of the honeycomb skeleton when the peak load was reached, resulting in the collapse of the whole layer of the honeycomb structure, which led to the collapse of the whole layer of the honeycomb skeleton. This led to the collapse of the whole layer of the honeycomb structure and a significant decrease in the bearing capacity, which confirmed the layer-by-layer damage characteristics of segmental cementitious honeycomb structures. In addition, the RA-AF values show that the loading rate has little effect on the crack type, which is almost unchanged with the increase of loading rate. These studies verify the feasibility of using honeycomb structure to support roadway with fast deformation speed and large deformation. It is of great significance to guide the application of honeycomb structure in deep roadway support engineering.